First record of Cyttarops alecto in Ecuador - Vivas-Toro, Isabela; Camacho, María A.; Burneo, Santiago F. (Therya Notes, 2024)
Cyttarops alecto Thomas, 1913 is one of the rarest Neotropical bat species found in biological collections. Here we report the first record of C. alecto for Ecuador, which represents a new genus and species of Emballonuridae for the country. This record is based on an adult male specimen from Yasuní National Park, Orellana, Northeastern Ecuador, which was held in a national mammal collection previously misidentified as Peropteryx macrotis. We provide a detailed description of the specimen and an updated distribution map for the species. We show the importance of reviewing and verifying identifications of voucher specimens in biological collections as they contribute to historical knowledge of distributions and biodiversity.